White encrustation produced from deer antler phosphate on prehistoric ceramics from Podunavlje - Kos, K.; Posilović, Hrvoje; Durman, Aleksandar; Ristić, Mira; Krehula, Stjepko (2015)
The composition and structure of the white pigments used in the encrustation paste on prehistoric ceramics is analysed and described. Encrustations, pigments and their use were studied chronologically, starting with their first appearance during the early Kostolac culture (3500-3000 bc, Copper Age), their very extensive use in the Vučedol culture (3000-2500 bc, Copper Age) and their final disappearance with the Pannonian complex of Encrusted Pottery (2000-1500 bc, Bronze Age). Most of the Kostolac and Vučedol culture material is from the Vučedol and Vinkovci Hotel localities. The Pannonian culture material is from the Grabrovac (Đakovo) locality. The encrustations were analysed by deep field optical microscopy, polarization microscopy, scanning electron microscopy with EDS, and XRD. Our investigation showed that from the very beginning to the end of the use of the encrustation technique in this area and by these cultures, the composition of the white paste was quite unique. The base material is produced by burning and powdering of deer antler. Crushed freshwater clam shells (Unio sp.) were a common addition to the phosphate paste
Projekt MZOS
Projekt MZOS
ENG